1. The problem statement, all variables and given/known data Find the general solution to the diff equation using undetermined coefficients y''-2y'-3y = 3te^-1 2. Relevant equations 3. The attempt at a solution r^2 - 2r -3 = 0 r = -1, 3 so y = c1 e^-t + c2e^3t + yp since e^-t already exists as a solution, i have to multiply my Yp by t to make sure i don't' end up with the same solution. So my Yp with the unknown coeffcient should be, yp = At^2e^-t should it be (At^2+bt+c)e^-t instead or something else? i've done it both ways and came up with wrong answers. I know what to do after figuring out yp, its just i can't get it right with ideas i have right now. Any help is greatly appreciated. Thank you!